Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 9 - Basic Algebra - 9.4 Order of Operations - 9.4 Exercises - Page 655: 56

Answer

$2\frac{1}{9}$

Work Step by Step

$(-\frac{2}{3})^2 - (\frac{1}{6} - \frac{11}{6} = \frac{4}{9} - (-\frac{10}{6}) = \frac{4}{9}+\frac{5}{3} = \frac{4+15}{9} = \frac{19}{9} = 2\frac{1}{9}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.